Macro and microscopic characters of Maerua oblongifolia (Forssk.) A. Rich leaf - Prabhakar, G.; Shailaja, K.; Kamalakar, P. (Current Botany, 2020)
The paper deals with a detailed investigation on the leaves of Maerua oblongifolia (Forssk.) A. Rich. which includes it’s morphological, anatomical and powder analysis. It is a low woody bushy under-shrub belonging to the family Capparaceae. The leaves are used in treatment of as fever, ear ache, stomach ache, skin infections, urinary calculii, diabetes mellitus, epilepsy, rigidity in lower limbs, and abdominal colic. The leaf amphistomatic, with mostly anamocytic, few tetracytic stomata. In transverse section of leaf is ribbed on either sides at midvein, epidermis one layered. Mesophyll differentiated into palisade and spongy tissues. Ground tissue of midvein differentiated into palisade, collenchyma and parenchyma. The midvien consists of one large oval shaped vascular bundles arranged are at the centre. Petiole in transverse section is circular adaxially small, grooved at centre and epidermis is having one layered, a single circular vascular bundle present at the centre, vascular bundle is enclosed by endodermis. The powder microscopic and organoleptic characters are also presented in this study. This study would helps as an appropriate source for authentification of the present studied drug.